Empowering Indonesia's Ageing Workforce: A Strategic Roadmap for Sustainable Economic Growth - Roziq, Mohammad; Warsida, Rotua Yossina; Raharja, Hadhi; Maryani, Maryani (Jurnal Ketenagakerjaan, 2024)
Indonesia is expected to reach its demographic dividend peak by 2035. After this period, the productive-age population will transition into an ageing population, increasing dependency on the working-age group. This demographic shift demands holistic policies to create age-friendly work environments, empower the elderly, and ensure inclusive protection to sustain Indonesia’s economy. By 2050, the population aged 65 and above will reach 56 million, with life expectancy increasing to 79.64 years. In 2023, approximately 53.93% of Indonesia’s elderly population remained employed. Although Presidential Regulation No. 88/2021 addresses the National Elderly Strategy, it requires revision to enhance the empowerment and protection of elderly workers. Learning from other countries, ASEAN nations like Singapore and Malaysia have enacted re-employment laws for workers over 60. At the same time, Japan and South Korea implement re-employment programs, training, and workforce placement for the elderly. To address the ageing population, Indonesia must develop a comprehensive national strategy, including re-employment schemes, skill development, entrepreneurship, social protection, and the silver economy. A five-year roadmap (2025-2029) outlines the strategy’s phased implementation: strengthening policies and public awareness in 2025, program implementation in 2026, expansion of re-employment and entrepreneurship in 2027, silver economy development in 2028, and program sustainability by 2029.